Photoinduced phase transition and relaxation in bare SrTiO3 single crystals - Jin, K. X. (2013)
The photoinduced insulator-metal phase transition and relaxation characteristics have been investigated in bare SrTiO3 single crystals. The photoinduced relaxation time constant after the irradiation shows an increase with increasing temperatures. The SrTiO3 single crystal has a cutoff wavelength and an absorption edge of spectrum at about 385 nm, which agrees well with the band gap. The photocurrent responsivity is 1.36 × 10−5 A/W at 300 nm wavelength. The relative change in resistance is more than above six orders at room temperature, possessing potential applications in ultraviolet sensitive and detecting devices